Paradigmatic Discord in US Arctic Policy - Matiyak, L. A. (Vestnik MGIMO-Universiteta, 2015)
The United States, as one of the five Arctic states, plays what seems at first glance a typical role in the Arctic through their regional policy that uses standard tactical maneuvers, which have proven themselves worthy in other areas of the globe. However, this role is played with unusual passiveness that can be attributed primarily to a lack of an Arctic identity. This is most evident upon comparison with other states of the Arctic "five", which are completely different from each other, and nevertheless are bound by a sense of belonging to the North. The Unites States is the only Arctic state that has not signed the United Nations Convention on the Law of the Sea, that has taken a firm stance on the sovereignty of the Northwest Passage, that risks increasing tensions with Canada, and that is not developing its icebreaker fleet, which is crucial to operations in the Arctic. This circumpolar strategic ambivalence of a powerful state, that is experienced in conducting foreign affairs, in itself presents significant room for research. Meanwhile, the region's importance is increasing in the changing international environment; it can become a "battlefield" due its strategic geopolitical position and at the same time the "main trophy"due to its abundant hydrocarbon potential. During the recent years, the Arctic has been gradually transforming into a "metaregion" for foreign affairs; its geographically limited borders have spread globally due to an increasing international presence in the Polar Region that has significant energy resources and transportation potential. This is confirmed by the emergence of new actors (including traditionally non-Arctic players), the change in agenda of multilateral discussions (traditional topics, such as protection of the fragile Arctic environment, indigenous peoples of the North, have been complemented with the new "challenges" of energy security, global warming, and militarization), and the strengthening of the institutional framework (the Arctic Council has been more and more influential). In light of the recent tension in Russian-US relations and the rising significance of the Polar Region, US Arctic policy should be the subject of an in-depth analysis of foreign-affairs experts and the government.